Parental Beliefs as a Factor in the Cognitive and Socio-Emotional Development of the Child - Natalia A. Rudnova; Dmitry S. Kornienko; Margarita N. Gavrilova; Yulia S. Shvedchikova (Lomonosov Moscow State University, 2024)
Background. Modern psychology of parenting offers various phenomena for study, including parental relations, parental attitudes, and parenting practices. The study of parental attitudes enables us to describe the cognitive aspect of the family environment in which the child develops. Previous studies have found a significant association between parental attitudes and the cognitive and socio-emotional development of children. However, their results are ambiguous and require further clarification. Objectives. The aim of this study is to analyze the connection between parental attitudes regarding the necessity of structuring the environment or supporting the child's spontaneous activity, and the indicators of the child's cognitive and socio-emotional development. In addition, the study examines the presence of confrontation between parents regarding the characteristics of upbringing and fostering. Study Participants. The main sample of the study consisted of 338 people, specifically parents of preschool children, aged from 23 to 65 years (M = 36.63, SD = 5.004), and their children aged from 53 to 81 months (M = 70.36, SD = 4.198). Methods. We developed three groups of statements to identify parental attitudes: 1) statements about the organization of the child's life; 2) statements about the role of play activities; 3) statements about confrontational attitudes within the family. Indicators of children's cognitive development were identified using J. Raven's Colored Progressive Matrices and subtests of the NEPSY-II method. Social-emotional features were identified with the "Test for Understanding Emotions". Results. Most parents consider a structured environment to be more important for the well-being of their child. In addition, research has shown that attitudes towards the positive impact of a structured environment are a strong predictor of a child's nonverbal intelligence. Similarly, attitudes towards the importance of spontaneous activity are predictors of auditory-verbal memory and the ability to switch tasks efficiently. Parental attitudes did not show any associations with the socio-emotional development of children. Conclusions. Parental attitudes play a significant role in child development. The belief in the need to structure the child's environment may have positive effects on the child's cognitive development. However, it does not affect social-emotional development. On the other hand, the belief in the need for spontaneous activity is more likely to be associated with lower levels of executive functioning in the child.